SPIN RODA SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN UNTUK MENGEMBANGKAN PERCAYA DIRI SISWA SEKOLAH DASAR - Zainiyah, Khikmatun; Rulyansah, Afib; Djazilan, Muhammad Sukron; Rahayu, Dewi Widiana (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to apply the Spin Wheel as an Alternative Learning Media to Develop Confidence in Elementary School Students. The subjects in this study were regular 5th grade students, upper class inclusion students, 5th grade teachers and upper inclusion teachers. The time of the research was carried out in May 2023 at one of the elementary schools in Surabaya, namely Sumur Welut I Elementary School. This research is acomparative qualitative research where this research is to compare two treatments or more than one variable. This research also requires information in the form of descriptive with a theory that is built based on the data obtained and also the data from the interpretation of scores into categories for comparison. Data collection techniques with observation, interviews, documentation and questionnaires. The research targets were 5th grade students, upper class inclusion students, 5th grade teachers and upper-class inclusion teachers. The purpose of this research was to develop students' self- confidence by applying the spin wheel media and to find out the effectiveness and quality of the spin wheel media. The method used in this study is using 4 stages including, observation, interviews, questionnaires and documentation. The results showed that the spin wheel media was effective and of good quality to be applied to regular 5th grade students and upper-class inclusion students.